1997
DOI: 10.1177/109135059700200309
|View full text |Cite
|
Sign up to set email alerts
|

Autoclave Emissions—Hazardous or Not

Abstract: Autoclaves used for sterilization and decontamination of biological materials operate at temperatures of 121°C or higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…mercury lead, arsenic, cadmium), dioxins and furans (Hossain, 2011). Hadar et al (1997) reported that a number of volatile organic compounds are released at low levels during sterilization. For most volatile organic compounds, these concentrations do not constitute an acute health hazard.…”
Section: Methodsmentioning
confidence: 99%
“…mercury lead, arsenic, cadmium), dioxins and furans (Hossain, 2011). Hadar et al (1997) reported that a number of volatile organic compounds are released at low levels during sterilization. For most volatile organic compounds, these concentrations do not constitute an acute health hazard.…”
Section: Methodsmentioning
confidence: 99%
“…Growing the malaria parasite in blood cultures forms congealed clumps, and so there was concern that the typical bleach solution may not penetrate enough to maintain an acceptable level of efficacy and cannot be autoclaved because of the release of toxic fumes. 10 While operating at the BSL-2 level, the team devised a protocol to continue decontaminating all blood culture waste with bleach but treat it as chemical waste and decontaminate the containment vessel at the facility exit. When the facility is used at the ACL-3 level in the future, the team plans to validate a new decontamination procedure using an antiseptic iodine solution within the BSC followed by steam sterilization.…”
Section: Resultsmentioning
confidence: 99%
“…Separate experiments (data not shown) showed weak growth on agar alone without the nitrocellulose membrane. The decomposition of agar ingredients (water-soluble polysaccharide) during sterilization could provide carbon and nitrogen sources for spore germination [ 89 , 90 ], enabling this low level of growth.…”
Section: Discussionmentioning
confidence: 99%